Assessment of Takayasu's arteritis activity by ultrasound localization microscopyResearch in context - Guillaume Goudot; Anatole Jimenez; Nassim Mohamedi; Jonas Sitruk; Lina Khider; Hélène Mortelette; Clément Papadacci; Fabien Hyafil; Mickaël Tanter; Emmanuel Messas; Mathieu Pernot; Tristan Mirault (EBioMedicine, 2023)
Summary: Background: Ultrasound localization microscopy (ULM) based on ultrafast ultrasound imaging of circulating microbubbles (MB) can image microvascular blood flows in vivo up to the micron scale. Takayasu arteritis (TA) has an increased vascularisation of the thickened arterial wall when active. We aimed to perform vasa vasorum ULM of the carotid wall and demonstrate that ULM can provide imaging markers to assess the TA activity. Methods: Patients with TA were consecutively included with assessment of activity by the National Institute of Health criteria: 5 had active TA (median age 35.8 [24.5–46.0] years) and 11 had quiescent TA (37.2 [31.7–47.3] years). ULM was performed using a 6.4 MHz probe and a dedicated imaging sequence (plane waves with 8 angles, frame rate 500 Hz), coupled with the intravenous injection of MB. Individual MB were localised at a subwavelength scale then tracked, allowing the reconstruction of the vasa vasorum flow anatomy and velocity. Findings: ULM allowed to show microvessels and to measure their flow velocity within the arterial wall. The number of MB detected per second in the wall was 121 [80–146] in active cases vs. 10 [6–15] in quiescent cases (p = 0.0005), with a mean velocity of 40.5 [39.0–42.9] mm.s−1 in active cases. Interpretation: ULM allows visualisation of microvessels within the thickened carotid wall in TA, with significantly greater MB density in active cases. ULM provides a precise visualisation in vivo of the vasa vasorum and gives access to the arterial wall vascularisation quantification. Funding: French Society of Cardiology. ART (Technological Research Accelerator) biomedical ultrasound program of INSERM, France.